Mechanisms of venetoclax resistance and solutions - Liu, Jiachen; Chen, Yidong; Yu, Lihua; Yang, Lihua (Frontiers in Oncology, 2022)
The BCL-2 inhibitor venetoclax is popular in the current treatment of hematologic diseases and is widely used either as monotherapy or in combination strategies. It has produced promising results in the treatment of refractory or relapsed (R/R) and aged malignant hematologic diseases. However, with clinical use, resistance to venetoclax has emerged. We review the mechanism of reduced dependence on BCL-2 mediated by the upregulation of antiapoptotic proteins other than BCL-2, such as MCL-1 and BCL-XL, which is the primary mechanism of venetoclax resistance, and find that this mechanism is achieved through different pathways in different hematologic diseases. Additionally, this paper also summarizes the current investigations of the mechanisms of venetoclax resistance in terms of altered cellular metabolism, changes in the mitochondrial structure, altered or modified BCL-2 binding domains, and some other aspects; this article also reviews relevant strategies to address these resistance mechanisms.